2011
DOI: 10.1177/0731684411431122
|View full text |Cite
|
Sign up to set email alerts
|

Stability of smart sandwich beams with cross-ply faces and electrorheological core subjected to axial loads

Abstract: In this article, an effort has been made to deal with stability analysis of a smart sandwich beam with cross-ply faces and ER core. An ER layer is adhered to the laminated composite beam to increase dynamic stability of the beam. Bingham's model is applied to model dynamic behavior of ER layer. A smart beam element is derived for the sandwich beam and finite element modeling is carried out. Transient response of the beam to an initial excitation is calculated using direct integration method. By analyzing the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Also, it was shown that the natural frequencies of the rotating sandwich beam increase with increase in rotating speed but the damping loss factors of the rotating beam decrease with increase in rotating speed. The stability analysis of smart sandwich beams with cross-ply composite face sheets and electro-rheological fluid as core materials subjected to axial loads was investigated numerically by Tabassian and Rezaeepazhand [15]. It was concluded that the stacking sequence and thickness ratio of elastic faces affect both static and dynamic stability of the sandwich beam.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was shown that the natural frequencies of the rotating sandwich beam increase with increase in rotating speed but the damping loss factors of the rotating beam decrease with increase in rotating speed. The stability analysis of smart sandwich beams with cross-ply composite face sheets and electro-rheological fluid as core materials subjected to axial loads was investigated numerically by Tabassian and Rezaeepazhand [15]. It was concluded that the stacking sequence and thickness ratio of elastic faces affect both static and dynamic stability of the sandwich beam.…”
Section: Introductionmentioning
confidence: 99%
“…Buckling, vibration and dynamic stability of a sandwich beam with MR fluid core layer has been investigated by Yeh and Shih [8]. Tabasian and Rezaeepazhand [9] considered the post-yield behavior of the ER fluid for the dynamic stability of a sandwich composite beam with an intermediate ER layer. They also [10] investigated the effect of Winkler elastic foundation on dynamic stability of the smart sandwich beam.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of electric field intensity and ER patch parameters on frequency response and modal loss factors are examined. The investigations of sandwich elements with ER core presented in works [7,8,9] are worth attention. The problem of sandwich plates with ER fluid core subjected to supersonic airflow is analysed in [7].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of sandwich plates with ER fluid core subjected to supersonic airflow is analysed in [7]. A sandwich beam with ER core resting on Winkler's elastic foundation under harmonic axial loads and a laminated composite beam with ER layer expressed by Bingham's model are analysed in works [8] and [9], respectively. Among other things, there was shown the significance of ER layer, which affects damping properties of structures, increases the critical loads and improves the dynamic stability.…”
Section: Introductionmentioning
confidence: 99%